KEPUTUSAN, SIKAP, DAN FAKTOR – FAKTOR YANG MEMENGARUHI PEMBELIAN TELUR AYAM RAS PADA RUMAH TANGGA PRASEJAHTERA - Andika Prasetio Nugroho; Yaktiworo Indriyani; Wuryaningsih Dwi Sayekti (Lampung University, 2021)
This study aimed to determine the decision making, attitudes and factors that affected underprivileged households on buying eggs in Bandar Lampung city. This research was conducted in Teluk Betung Timur. The research method used in this research was survey method. The research data consisted of primary and secondary data. Primary data was collected by conducting interviews with 75 underprivileged households. Secondary data was obtained by literature study. The sampling technique used in this study was simple random sampling. The research data was analyzed descriptively and qualitatively, by Fishbein multiattribute model and multiple linear regression analysis. The results obtained from this study showed that consumers decided to buy eggs at the sales location through the need recognition stage, information search stage, alternative evaluation stage, purchase decision stage and post purchase evaluation stage. The price of chicken eggs was the benefit, main focus and the most considered on choosing a location to buy eggs. Consumers prefer buying eggs at grocery stalls compared to traditional markets and modern markets. Together, the price of eggs, household income, number of household members, the price of free-range chicken eggs, the price of purebred chicken, the price of beef, the price of tempeh, tofu, salted fish and cooking oil had a significant effect on purchasing eggs. Factors that significantly influence the purchase of eggs by underprivileged households in Bandar Lampung were the price of eggs and the number of household members.Key words: attitude, decision, eggs, factors